Evaluation of Electronic Device No-Failure - Balaisis, R.J.; Eidukas, D.; Navikas, D. (Elektronika ir Elektrotechnika, 1997)
There is given a survey of dynamic action influence on electronic device no-failure. Unacceptability of widespread methods of digital device no-failure evaluation is presented. There is offered more acceptable method for calculation of failure intensity of electronic device components.